Climate Change, Coasts and Coastal Risk - Roshanka Ranasinghe (Ed.); Ruben Jongejan (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The combination of coastal climate change impacts and their effects on the ever-increasing human utilization of the coastal zone will invariably result in increasing coastal risk in the coming decades. However, while economic damage (potential consequence) caused by climate change-driven coastal inundation and erosion (potential hazard) is likely to increase, foregoing land-use opportunities in coastal regions and protecting or nourishing coasts is also costly. Managing the risk of coastline recession is therefore a balancing act. To avoid unacceptable future risks, it is imperative that risk-informed and sustainable coastal planning/management strategies are implemented sooner rather than later. This requires the development of methods for comprehensive coastal risk assessments which combine state-of-the-art consequence (or damage) modeling and coastal hazard modeling. This Special Issue contains 13 papers aimed at addressing this challenge.